Managers' Discretionary Adjustments: The Influence of Uncontrollable Events and Compensation Interdependence - Bol, Jasmijn C.; Hecht, Gary; Smith, Steven D. (Contemporary Accounting Research, 2015)
Abstract Discretionary bonus adjustments allow managers to restore the alignment of employee effort and compensation when bonus amounts are based on noisy objective performance measures. The implications of discretionary adjustments for employees' future efforts and fairness perceptions present important trade‐offs for managers to consider. Adjustments may be used to motivate different types of effort in future periods, but may also create perceptions of unfairness among employees who are not affected by negative events. This study examines the joint influence of the likelihood of future negative uncontrollable events and compensation interdependence (i.e., the extent to which one employee's compensation influences others' compensation) on managers' willingness to make adjustments for the effect of a negative uncontrollable event on a single employee. In our experiment, we manipulate the likelihood of future uncontrollable events and whether bonuses are determined individually or are drawn from a shared bonus pool. Results show that managers are less willing to adjust when the likelihood of future events is high to avoid setting a precedent, thereby motivating employees to adapt to changing conditions. We also find that managers are less willing to adjust, regardless of event likelihood, when compensation interdependence is high, to avoid demotivating unaffected employees. Finally, we find that participants' general attitudes toward compensation significantly influence their adjustment decisions beyond the effects of our independent variables. Our results highlight the unique nature of discretionary adjustments, help explain findings from previous research, and demonstrate important considerations managers must make when using the flexibility provided to them in pay‐for‐performance contracts.